A new species and morphological notes on the remarkable termitophilous genus Austrospirachtha Watson from Australia (Coleoptera: Staphylinidae: Aleocharinae) - Zilberman, Bruno; Pires-Silva, Carlos M. (Zootaxa, 2023)
Termitophilous rove beetles in Australia encompass diverse genera and species from several tribes in Aleocharinae. While some taxa have been well-documented, others remain poorly known due to the scarcity of available material. The existing knowledge of Austrospirachtha Watson for instance, is based solely on Austrospirachtha mimetes, described from two specimens collected in an old termite mound. The genus is known for its highly developed physogastry and potential mimicry adaptations. Herein, we present the description of a new species, Austrospirachtha carrijoi sp. nov., representing the second known species for the genus.